Supporting Distance Learners: Making Practice More Effective - Keryn Pratt (Flexible Learning Association of New Zealand, 2015)
This paper reports on a qualitative evaluation of the postgraduate courses offered by distance in one university department. The types and amount of support provided to students was evaluated and compared with Simpson's (2008a) Proactive Motivational Support model (PaMS). While students were largely satisfied with the support they received during their studies, their perceptions of the levels and effectiveness of that support varied. They also perceived a variation in the levels of support between individual courses. A number of areas where support could be improved were identified, including those that met the characteristics of the PaMS model.